Konflik Internal partai Politik Studi Partai Demokrat Periode 2020-2021 - Erwin Syahrial; Asran Jalal (Universitas Nasional, 2023)
Political parties are formed due to coalitions of several parties, not only having common goals and interests but also individual interests. Parties become a representation of diverse identities and interests, members who have the most similar or close views and preferences have the urge to gather together and create sub-groups or factions within a party. Within the party, factions work together to produce party unity, while competing for control of the party. But not a few end up splitting. The internal conflict of the Democratic Party surfaced to the public when an Extraordinary Congress was held in 2021 which resulted in a rival management. This research provides an overview of the causes of conflict, the characteristics of conflict and the approach model in conflict resolution. The research method is qualitative with an analytical descriptive approach. The research uses political party theory to explain the background of party formation and personalization symptoms that are a problem in party institutionalization. Intra-party conflict theory is used to understand the conflict model that occurs. The results revealed the existence of faction factors, party personalization and power relations have become sources and causes of conflict. The characteristics of the conflict have made this conflict not so widespread and enlarged. Elite conflict, which is premature and pragmatic, and the element of power rationality are factors that can answer why the conflict takes place and finishes quickly. In the conflict resolution model, both camps took a third party, namely the government and the court, to decide the dispute. Partai politik terbentuk karena koalisi beberapa pihak, tidak hanya memiliki tujuan dan kepentingan bersama tetapi juga kepentingan individu. Partai menjadi representasi beragam identitas dan kepentingan, anggota yang memiliki pandangan dan preferensi paling mirip atau dekat memiliki dorongan berkumpul bersama dan membuat sub kelompok atau faksi di dalam sebuah partai. Di dalam tubuh partai, faksi bekerja sama untuk menghasilkan persatuan partai, sekaligus bersaing untuk mengambil kendali partai. Namun tidak sedikit yang berakhir dengan perpecahan. Konflik internal Partai Demokrat mengemuka ke publik saat digelar Kongres Luar Biasa pada 2021 yang menghasilkan kepengurusan tandingan. Penelitian ini memberikan gambaran tentang penyebab konflik, karakteristik konflik dan model pendekatan dalam penyelesaian konflik. Metode penelitian bersifat kualitatif dengan pendekatan deskriptif analitis. Penelitian menggunakan teori partai politik untuk menjelaskan latar pembentukan partai dan gejala personalisasi yang menjadi soal dalam pelembagaan partai. Teori konflik intra partai digunakan untuk memahami model konflik yang terjadi. Hasil penelitian mengungkapkan keberadaan faktor faksi, personalisasi partai dan relasi kekuasaan telah menjadi sumber dan sebab konflik. Karakteristik konflik telah menjadikan konflik ini tidak begitu meluas dan membesar. Konflik elite, bersifat prematur dan pragmatis dan unsur rasionalitas kekuasaan merupakan faktor yang dapat menjawab mengapa konflik berlangsung dan selesai dengan cepat. Dalam model penyelesaian konflik kedua kubu mengambil pihak ketiga yaitu pemerintah dan pengadilan dalam memutuskan sengketa yang terjadi.